Disposable Capacitive Biosensor for Dopamine Sensing. Issue 40 (27th October 2020) - Dhanjai,; Yu, Nancy; Mugo, Samuel M.
Abstract: The present paper reports fabrication of a disposable tyrosinase (Tyr) biosensor for rapid detection of dopamine. Tyr immobilized polyaniline/carbon nanotubes/cellulose nanocrystals (Tyr@PANI/CNTs/CNC) conductive film was fabricated on polyvinyl acetate (PVA) transparency and characterized by scanning electron microscopy (SEM) and cyclic voltammetry (CV). Tyr catalyzed dopamine oxidation to o ‐dopaquinone was analysed by CV and capacitance was recorded. PANI/CNTs/CNC film acted as a suitable enzyme support which also showed its synergistic effect in accelerating the biocatalytic oxidation reaction. Tyr biosensor exhibited excellent reproducibility, and specificity towards dopamine with correlation coefficient ( R 2 ) of 0.9508 and limit of detection (LOD) of 1.57 nM within linear concentration range of 7–1000 mM. The study suggested practical utilization of disposable biosensor towards dopamine detection in biological fluids. Abstract : Fabrication of a disposable enzyme immobilized capacitive biosensor (Tyr@PANI/CNT/CNC) for dopamine detection where dopamine acts as a suitable substrate for tyrosinase (Tyr). The Tyr biosensor manifests selectivity towards dopamine detection and catalyzed its oxidation to o ‐dopaquinone.